Hyaluronic acid as a pulpotomy material in primary molars: an up to 30 months retrospective study - KOYUNCU, ÖZGE; MENTEŞ, ALİ RECAİ (My University, 2024)
Background: The aim of this retrospective study was to determine the long-term clinical and radiographic success of our previous randomized clinical trial and to compare the success of hyaluronic acid, with the widely used formocresol and ferric sulphate agents. Methods: This retrospective study is the extension of the 1-year survey of our randomized clinical trial that had compared the effectiveness of a hyaluronic acid pulpotomy over formocresol and ferric sulphate pulpotomies and included clinical and radiographic evaluations with a follow-up period of over 24 months for 44 children who applied to our clinic between May 2019 and September 2019. Long-term clinical and radiographic data were obtained from the periodic files of our department, wherein each tooth’s file was examined to identify any clinical and radiographic findings. Descriptive statistics and Pearson’s chi-square tests were used to evaluate the data. Statistical significance was considered as p 24 months. None of the teeth in the hyaluronic acid group showed any clinical findings at > 24 months. Conclusions: Hyaluronic acid pulpotomies exhibited comparable success rates to formocresol and ferric sulphate materials spanning over 24 months examinations. Because of convenient accessibility and applicability of hyaluronic acid, it may be recommended as a promising alternative medicament for pulpotomy treatments of primary molars. However, further long-term follow-up human studies are needed to better understand the effect of hyaluronic acid on the dental pulp of human primary molars. Keywords Pulpotomy, Primary molars, Hyaluronic acid, Formocresol, Ferric sulphate, Retrospective study
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Ferric sulphate; Formocresol; Hyaluronic acid; Primary molars; Pulpotomy; Retrospective study; Pulpotomy; Primary molars; Hyaluronic acid; Formocresol; Ferric sulphate; Retrospective study